Analysis of Facility Maintenance at General Ahmad Yani International Airport Cargo Terminal Semarang - Zulfa Naufal Asy-Syauqi; Zenita Kurniasari (CV. Rayyan Dwi Bharata, 2023)
Cargo terminal maintenance is one of the responsibilities of PT. Angkasa Pura Logistics. PT. Angkasa Pura Logistics is a company engaged in land, sea and air transportation management services as well as cargo and postal inspection. The purpose of the study was to determine the maintenance of SOP cargo terminal facilities owned by PT. Angkasa Pura Logistics is used as a guideline for officials/technicians in carrying out facility maintenance. General Ahmad Yani International Airport cargo terminal Semarang. This study uses a type of qualitative research. The data used in this research are primary data and secondary data. Primary data obtained by conducting observations and interviews, secondary data obtained through documentation. Data analysis in this study used a qualitative descriptive method with the Miles and Huberman model, namely reducing data, presenting data, and drawing conclusions/verification. To test the validity of the data the author uses the triangulation method. The results showed that the condition of the facilities in the Terminal was in good condition. Systematic maintenance of facilities at the Cargo Terminal is carried out according to the procedures and schedules that have been made. the duties and roles of the cargo service supervisor in carrying out their performance, namely overseeing several new facility conditions every day which later if damage occurs, it will be reported in the form of weekly recapitulations. There was damage to one of the facilities at the cargo terminal in the cargo terminal courtyard, namely cracks in the floor of the courtyard and loss of marking lines. The solution is to present the results of the report at a conference or coordination meeting with superiors or related institutions and it is necessary to invite or bring in superiors or related institutions to observe directly in the field so that you will find out directly the damage to facilities at the cargo terminal so that it is immediately followed up.